In the Wake of the Global Crisis : Evidence from a New Quarterly Database of Export Competitiveness - Gaulier, Guillaume; Santoni, Gianluca; Taglioni, Daria; Zignago, Soledad (World Bank, Washington, DC, 2014)
Over the past two decades, international trade has become a privileged engine of growth for much of the developing world. With the global economy evolving continuously and rapidly, countries must pay close attention to their positioning on the map of global trade and production. Within this framework, countries must also become aware of how they fare relative to competitors and to their past export performance. Of particular importance is the extent to which their performance is driven by exporter own supply-side capacity as opposed to external or compositional factors, including product and geographical specialization and how these trends compare across countries. This paper describes a new initiative that uses quarterly data for 2005q1-2013q1 to compute comparable indicators of export performance for 228 countries and territories. The database, the Export Competitiveness Database, reveals interesting patterns in trade performance. Export performance, stripped of compositional effects, was strongest for countries from the Asia and Pacific region, on average. Moreover, such performance was almost entirely driven by exporting country specific factors, with changes reflecting growth in volume rather than price developments. All emerging and developing regions have, on average, improved export performance. The indicators in the database trace the legacy of supply-side capacity and the overall export performance of the double-dip recession in the euro area. An illustrative set of results suggests that the paper's measure of competitiveness correlates to a country's nominal and real effective exchange rate, factors that are commonly perceived as important determinants of competitiveness.